Pengaruh Mobilisasi Dini terhadap Penurunan Nyeri Pasien Post Operasi Bedah: Scoping Review (Lembaga Pengembangan Kinerja Dosen, 2026)
Postoperative pain is a common clinical condition experienced by patients after surgical procedures and may hinder the recovery process if not properly managed. In addition to pharmacological therapy, safe and effective non-pharmacological interventions are needed, one of which is early mobilization. This study aimed to analyze the effect of early mobilization on pain reduction in postoperative surgical patients. A scoping review method was conducted based on the Arksey and O’Malley framework. Literature searches were performed using ScienceDirect, PubMed, and Google Scholar databases with a PICO strategy, including articles published within the last five years. From a total of 167,948 identified articles, 10 studies met the inclusion criteria and were included in the analysis. The results showed that early mobilization performed gradually and according to patients’ clinical conditions had a significant effect on reducing postoperative pain intensity. In addition, early mobilization was associated with improved comfort, enhanced functional recovery, and faster postoperative rehabilitation without increasing the risk of complications. Although variations were found in the timing and type of mobilization across studies, overall evidence supports that early mobilization is safe and effective. In conclusion, early mobilization can be recommended as an evidence-based nursing intervention for postoperative pain management.